Electronic Evidence in Criminal Prosecutions: Admissibility, Authenticity and the Future of Fair Trials - Suvija, A. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
In today’s digital world, rapid technological advancement, especially the increasing use of artificial intelligence has significantly influenced almost every field, including commercial, civil, political and judicial systems. While technology has improved efficiency and connectivity, it has also led to a rise in computer related crimes and as well as other crime networks. As a result, reliance on digital or electronic evidence in criminal prosecutions has become unavoidable. However, admitting material as evidence is not a simple task. Mainly when it comes to electronics, the standard should be high. Courts must carefully evaluate such evidence in accordance with established legal principles to ensure its admissibility, authenticity, and integrity. This paper explores the legal position in Sri Lanka regarding the use of electronic evidence in criminal proceedings. It analyses whether existing laws, including the Evidence Ordinance (special provision amendment 1995), the Electronic Transactions Act, and other related legislation are adequate to address the challenges posed by electronic evidence. The paper highlights several weaknesses and gaps within the current legal framework, particularly in relation to technological developments and procedural safeguards. In addition, the study adopts a comparative approach by examining how the United States and India regulate and assess electronic evidence in criminal trials. Through this comparison, the paper identifies best practices that may be adopted within the Sri Lankan legal system. Using a doctrinal research method, the paper critically analyses Sri Lankan statutory provisions alongside the black-letter law of the two comparative jurisdictions, supported by selected judicial decisions. The paper ultimately argues that Sri Lanka’s current legal framework requires timely reform to keep pace with technological change. As technology continues to change every second, stronger evidentiary and procedural safeguards are vital to ensure reliable evidence, protect fair trial guarantees, and maintain public confidence in the criminal justice system.
Keywords: Electronic evidence; Criminal trials; Authenticity; Admissibility; Fair trials